Isolated Mayer–Rokitansky–Kuster–Hauser syndrome (MRKH): Case Report - Mondale Saputra; Eka Putri (Universitas Andalas, 2023)
Background:Mayer–Rokitansky–Kuster–Hauser syndrome (MRKH) is a rare complex of congenitalmalformations characterized by aplasia of the uterus and upper (two-thirds) vagina in a woman with normalovaries and fallopian tubes, secondary sexual characteristics and a 46XX karyotype. The clinical symptoms ofMRKH syndrome are usually primary amenorrhea but with normal thelarche and adrenarche, as well as sexualintercourse disorders and infertility.Case report:In this case, a 22-year-old nulliparous woman with a female phenotype and normal secondary sexgrowth presented with primary amenorrhea and difficulty in sexual intercourse. On internal examination, thelength of the vagina was 4 cm and the cervix was not palpable. Transvaginal ultrasound examination did not showa picture of the uterus, but both ovaries were normal size and there were several follicles. Diagnostic laparoscopyshowed bilateral ovaries with intact tubes, but no uterus.Conclusion: Women with MRKH syndrome usually have normal ovarian function and usually present withprimary amenorrhea. Treatment of MRKH syndrome must include sexological care of the patient and hispartner.6The American College of Obstetricians and Gynecologists (ACOG) recommends dilation therapy as firstlinetreatment and vaginoplasty surgery should be performed for patients who have failed dilation therapy.